Brian Cadd. - Cadd, Brian (Brian George), 1946- ([Australia]: Brian Cadd.)
"Brian George Cadd (born 29 November 1946, Perth, Western Australia) is an Australian singer-songwriter, keyboardist, producer and record label founder, a staple of Australian entertainment for over 50 years, he has performed as a member of The Groop, Axiom, Flying Burrito Brothers and solo. He was briefly called Brian Caine in late 1966, when first joining The Groop."
Title from title screen (viewed on 7 June 2016)
Mode of access: Available Online. Address as at 14/06/2016
Selected for archiving
Keywords: Cadd, Brian -- 1946-; Rock musicians -- Australia; Singers -- Australia -- Portraits; Australian